Circuit training based futsal passing training model - Dahliana Dahliana; M. Haris Satria; Bayu Hardiyono; Selvi Atesya Kesumawati (Universitas Sriwijaya, 2025)
Research Problems: In futsal games, every player must absolutely master basic passing techniques. However, players often feel bored quickly if the basic passing technique material is not given variations during training so that players do not perform passing techniques properly and correctly. Research Objectives: The purpose of this research is to develop a circuit training-based futsal passing training model and test the effectiveness of developing the circuit training-based futsal passing training model. Methods: The method used is the ADDIE method (analysis, design, development, implementation, and evaluation) with 65 research subjects consisting of 15 Palembang City futsal athletes and 50 Palembang Academy Bigreds futsal athletes. The instrument in this study used a questionnaire. Results: The results of expert validation consisting of three experts, namely 1 futsal academicist, 1 futsal practitioner and 1 futsal coach, obtained a score of 93.3% and the results of the small-scale trial obtained an average score of 94.33%, and the value of the large-scale trial had a score of 93.18%. Conclusion: In this case, it can be concluded that the circuit training-based futsal passing training model that has been developed is already in the very good category and can be applied to improve the ability of futsal athletes in Palembang City.